Penggunaan Metode Prototype dalam Pengembangan Aplikasi Monitoring dan Evaluasi Terhadap Renja SKPD Kab Lombok Tengah - Fahmi, Hairul; Murniati, Wafiah (STMIK Budi Darma, 2022)
The process of monitoring and evaluation in a government agency, especially Badan Perencanaan Pembangunan Daerah (BAPPEDA) of Lombok Tengah Regency is one of the most important things to do. The process of monitoring the implementation of work is carried out to obtain facts, data, and information in the process of achieving goals. Bappeda Lombok Tengah in the process of implementing monitoring and evaluation still uses the conventional system by collecting SKPD files on a quarterly basis which causes the process to be inefficient. Therefore the application is very necessary. The purpose of this research is to produce an application to facilitate the monitoring and evaluation of the current year's RENJA. The system design/development method used is the prototyping method. The implementation of the prototype method is carried out in 3 (three) stages, the first stage is listening to system users related to system requirements, the second stage is making prototype interfaces and the third is testing the prototype interface that has been proposed by the user. In this study, the system will be tested with usability testing in the form of a questionnaire. The test consists of 3 assessments, namely system quality, information quality and service quality. to get feedback from users. Results of System Testing using a questionnaire method involving 10 respondents reached 87% which indicates that the RENJA Information system is very suitable for use by users. With this application, Bapeda can monitor the Work Plan of each SKPD and can provide an assessment of the realization of DPA-SKPD quickly, precisely and efficiently.